Techno-economic-environmental analysis of selecting piezoelectric tiles to use in a subway station (A case study) - Mohammad Hossein Jahangir; Nasrin Rashvand; Mojtaba Rezaeifard (Energy Strategy Reviews)
The growth in urban population has led to an increase in vehicular traffic, which raises energy consumption and results in a growth in greenhouse gas emissions. This has led to an increase in the use of public transportation, most especially the subway, where there has been a growth of 9 % in the annual number of subway passengers in the capital city of Tehran, Iran. This sets a higher demand for energy supplies, especially for lighting in subway stations. Various technologies have been used in supplying energy, and the most recent include piezoelectric tiles.This study is focused on Shahid Beheshti metro station, one of Tehran's most frequented stations. Using DesignBuilder software, the electrical load of the station was determined to be over 2 TWh/year. The required quantity of piezoelectric tiles was then determined using the HomerPro software. It was found that the optimal solution is the installation of 36 Waynergy piezoelectric tiles, which provide about 95.8 % of the energy needed by Shahid Beheshti metro station, reducing more than 70 % of carbon dioxide emissions.In the following, to ensure the correctness of the results and further investigation, the performance of this tile under 3 important parameters of population change, Change of working hours and passenger peak time, has been examined with 5 different scenarios.